Plastic bronchitis in a child with acute dyspnea and atelectasis: A case study - K, Sunkonkit; H, Klibngern; P, Mahanupab; S, Reungrongrat (Biomedical Sciences and Clinical Medicine, 2020)
Plastic bronchitis is an uncommon pathologic cast formation in the tracheobronchial tree. A bronchial cast can cause a range of conditions ranging from mild to severe that can lead to airway obstruction. We describe a previously healthy one-year-old boy who developed acute left lung atelectasis and respiratory distress due to plastic bronchitis. He pre- sented with a high-grade fever and productive cough. His chest x-ray showed total left lung atelectasis. His condition did not rule out the presence of a foreign body in the airway or an obstruction due to secretion. Plastic bronchitis ob- structing the left main bronchus was diagnosed and removed by rigid bronchoscopy. Bronchoscopy was crucial in this case for both diagnosis and therapeutic cast removal; however, understanding of the regulation of mucus production and clearance is vital for the prevention of new secretion obstructions.